Analisis Faktor-Faktor yang Mempengaruhi Alokasi Infak Rumah Tangga: Studi Kasus di Desa Pasir Eurih, Kecamatan Tamansari, Kabupaten Bogor - Myrella Velika Amanta; Wiwiek Rindayati; Laily Dwi Arsyianti (AL-MUZARA'AH, 2014)
Indonesia is one of countries with the most populous Muslim in the world. Poverty that strikes Muslims is an irony considering Islam is the only divine religion which explicitly requires his people to dispense zakah. Therefore, Zakah, Infaq, and Sadaqah (ZIS) is the potential solution to eradicate poverty in Indonesia. Infaq can be an alternative solution to alleviate poverty through income equalization. This study analyses factors that affect the household’s charity allocation using Ordinary Least Square (OLS) method and behavior of charity allocations on household using descriptive analysis. Result shows that altruism, income and formal education affect household’s charity allocation. These three factors positively influence the amount of household’s charity. On the other hand, behavior on charity allocation shows a good respond even though it is not yet a priority.